Exhaustion of domestic remedies under Art. 35 of the European Convention for the Protection of Human rights and Fundamental Freedoms - Kirsh, Stefan; Кірш, Стефан; Кирш, Стефан (Одеса : Фенікс, 2013)
The article is devoted to the analysis of the role of national authorities in the guaranteeing of human rights and freedoms, estimated by the European Convention for the Protection of human Rights and fundamental freedoms, and the activity of the Constitutional Court of germany as a guarantee of these rights.

Стаття присвячена аналізу ролі національної влади в забезпеченні прав і свобод людини, закріплених Європейською конвенцією про захист прав людини та основоположних свобод, зокрема діяльності Федерального Конституційного Суду ФРН як гаранту цих прав.

Статья посвящена анализу роли национальных властей в обеспечении прав и свобод человека, закрепленных европейской конвенцией о защите прав человека и основных свобод, в частности деятельности Федерального Конституционного Суда ФРГ как гаранта этих прав.
Die rechtswegerschöpfung nach Art. 35 EMRK und die rolle des Bundesverfassungsgerichts
Kirsh S. Exhaustion of domestic remedies under Art. 35 of the European Convention for the Protection of Human rights and Fundamental Freedoms / S. Kirsh // Правове забезпечення ефективного виконання рішень і застосування практики Європейського суду з прав людини : матер. 2-ї Міжнар. наук.-практ. конф. (Одеса, 20-21 вересня 2013 р.) / за ред. С. В. Ківалова ; НУ «ОЮА». – Одеса : Фенікс, 2013. – С. 260-267.
Keywords: human rights; Constitutional Court of Germany; exhaustion of domestic remedies; права людини; Федеральний Конституційний Суд ФРН; вичерпання внутрішніх засобів правового захисту; права человека; Федеральный Конституционный Суд ФРГ; исчерпание внутренних средств правовой защиты